Diffusion tensor imaging of the sural nerve in normal controls() - Kim, Boklye (Clin Imaging, 2014)
OBJECTIVE: To develop a diffusion tensor imaging (DTI) protocol for assessing the sural nerve in healthy subjects. METHODS: Sural nerves in 25 controls were imaged using DTI at 3 T with 6, 15, and 32 gradient directions. Fractional anisotropy (FA) and apparent diffusion coefficient (ADC) were computed from nerve regions of interest co-registered with T(2)-weighted images. RESULTS: Coronal images with 0.5(RL)×2.0(FH)×0.5(AP) mm(3) resolution successfully localized the sural nerve. FA maps showed less variability with 32 directions (0.559±0.071) compared to 15(0.590±0.080) and 6(0.659±0.109). CONCLUSIONS: Our DTI protocol was effective in imaging sural nerves in controls to establish normative FA/ADC, with potential to be used non-invasively in diseased nerves of patients.